STUDI KASUS TENTANG PESERTA DIDIK YANG BERKEPRIBADIAN MASKULIN DI SMP NEGERI 2 SUNGAI RAYA - Pratiwi, Popy; Wicaksono, Luhur; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe general problem of this research was â€˜to find a way to help students discovered their masculinityâ€. The sample was all of the students in class IX of SMP Negeri 2 sungai raya. The purpose of this research was to analyze the factor that caused masculinity in students class IX of SMP Negeri 2 sungai raya.This research is essentially beneficial to developed counseling and guidance theory especially individual counseling. The subject of this research was two students whom has masculinity. The method of this research was descriptive and classified as case study. Technique of data collecting was done by observation, interview, and home visit. The factors contribute in this case was fisiological factor which was the students had masculine appearance and masculine behavior . The psychological factor was linked to the lack of gender awareness, the lack of religiousity, and the unknown concept of discovering oneself. The last is sosiological factor which was linked to parents, scholl, and society. The counseling model used in this research was behavioural model using systematical desentitation technique.the sample appearance tell so much about her masculinity, she had masculine haircut, only get along with male friends, often get in fight, and curse a lot.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Â Keywords: Case Study, Masculinity, Students